A Common Good Perspective on Diversity. Issue 2 (4th April 2020) - Frémeaux, Sandrine
ABSTRACT: Drawing upon the theoretical debate on the concept of common good involving, in particular, Sison and Fontrodona (2012), I aim to show how the common good principle can serve as the basis for a new diversity perspective. Each of the three dominant diversity approaches—equality, diversity management, and inclusion—runs the ethical risk of focusing on community or individual levels, or on particular disciplines—economic, social, or moral. This article demonstrates that the common good principle could mitigate the ethical risks inherent to each of these diversity approaches. There are three positive aspects to a comprehensive common good perspective: 1) it includes considering different community levels, which it connects by subsidiarity, 2) it embraces the moral, social, and economic fields, which it connects by teleological hierarchy, and 3) it avoids the risk of exclusion by generating a sense of solidarity.